2012
DOI: 10.5539/ijps.v4n2p206
|View full text |Cite
|
Sign up to set email alerts
|

Does Red Lipstick Really Attract Men? An Evaluation in a Bar

Abstract: Previous research has demonstrated that the color red increases the attractiveness of women. It has also been found that makeup increases perceived women' attractiveness for men and was associated with perceived greater interest for the opposite sex. We hypothesized that women wearing red lipstick would be more favorably approached by men. Female confederates wearing red, pink, brown and no lipstick were seated in bars on Wednesday and Saturday nights in a popular spot on the West Atlantic coast of France. Eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 13 publications
4
25
0
Order By: Relevance
“…Finally, the colour manipulation in the current experiment involves colour changes to large regions such as the lips or eyes but does not consider the role of other makeup such as foundation, which would influence perceptions of skin evenness. As colour changes to regions such as the lips can have corresponding effects on judgements related to attractiveness (Guéguen, 2012;Stephen & McKeegan, 2010), our findings are still consistent with the proposal that colour changes related to makeup have corresponding negative effects on a specific component of female social dominance (i.e. leadership).…”
Section: Discussionsupporting
confidence: 89%
“…Finally, the colour manipulation in the current experiment involves colour changes to large regions such as the lips or eyes but does not consider the role of other makeup such as foundation, which would influence perceptions of skin evenness. As colour changes to regions such as the lips can have corresponding effects on judgements related to attractiveness (Guéguen, 2012;Stephen & McKeegan, 2010), our findings are still consistent with the proposal that colour changes related to makeup have corresponding negative effects on a specific component of female social dominance (i.e. leadership).…”
Section: Discussionsupporting
confidence: 89%
“…Empirical support has been found for this premise, using both self-report and behavioral indicators of attraction (Elliot & Niesta, 2008;Elliot, Tracy, Pazda, & Beall, 2013;Guéguen 2012a;2012b;2012c;Guéguen & Jacob, 2012;2103;2014;Lin, 2014;Pazda, Elliot, & Greitemeyer, 2012;2014;Re, Whitehead, Xiao, & Perrett, 2011;Roberts, Owen, & Havlicek, 2010;Stephen & McKeegan, 2010;cf. Lynn, Giebelhausen, Garcia, Li, & Patumanon, in press) 1 .…”
mentioning
confidence: 91%
“…This knowledge may be used not only in perspective of mate choice but also in social contexts. For instance, (Guéguen, 2012), showed that women's ornamentation of lips by red lipstick may influence a number of interpersonal contacts with men and decrease the amount of time needed for first contact with opposite sex individuals. Moreover, Guéguen and Jacob (2012) revealed that using red lipstick by female waitresses increased a number and amount of tips given by male (but not female) customers.…”
Section: Discussionmentioning
confidence: 99%